Target range of motion at 3 months after arthroscopic rotator cuff repair and its effect on the final outcome. (15th September 2017) - Tonotsuka, Hisahiro; Sugaya, Hiroyuki; Takahashi, Norimasa; Kawai, Nobuaki; Sugiyama, Hajime; Marumo, Keishi
Purpose: The postoperative protocol after arthroscopic rotator cuff repair (ARCR) is still controversial. Some surgeons recommend slower rehabilitation in order to improve the integrity of the repair, while others prefer early range-of-motion (ROM) exercise to avoid postoperative stiffness. The purpose of this study was to determine target ROM (T-ROM) measurements at 3 months after ARCR that are predictive of eventual full recovery without structural failure. Methods: The cases consisted of 374 shoulders in 360 patients who underwent primary ARCR and were followed up for at least 2 years. Forward flexion (FF) and side-lying external rotation (ER) were measured preoperatively at 3, 6, 9, 12, and 24 months after surgery, and the patients were divided into six subgroups according to the values for each type of ROM at 3 months (ROM-3M). In each subgroup, the final ROM at 24 months after surgery was compared to determine the T-ROM. The average ROMs with time and re-tear rate were then compared between the under-T-ROM and over-T-ROM groups. Results: The only significant difference in FF was between the 120–129° and 110–119° ROM-3M groups. Therefore, the T-ROM for FF was determined to be 120°. Similarly, the T-ROM for ER was determined to be 20°. Each ROM in the over-T-ROM group was significantly better than that in the under-T-ROM group at all assessments. There was no significant difference in the re-tear rate between the groups. Conclusion: To acquire sufficient ROM in 2 years without high re-tear rate, a target FF of 120° and ER of 20° should be achieved within 3 months after surgery.